Energy Efficient Scheme for Cellular Network Using G-Leach - Pradeep, R.; Elamathi, K.; Priyavadhani, G.; Suganya, E. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
This paper proposes an energy efficient scheme for cellular network using G-LEACH (Genetic Low Energy Adaptive Clustering Hierarchy). By using the genetic algorithm based upon adaptive clustering protocol the energy consumption of the every node can be reduced and then the lifetime of each node in the cellular network can be increased. The proposed algorithm is compared with LEACH (Low -Energy Adaptive Clustering Hierarchy). The G-LEACH is implemented by using three phase. They are preparation phase, set-up phase, and at last steady-state phase. The preparation phase is the initial phase of the algorithm, in this phase the cluster head extraction process is executed by within all the random cellular network nodes. All nodes send the condition and position within the cluster as a resubmit message to the base station of the cellular network. By using the resubmit message base station exploring the node as cluster head which has the most eminent energy for foster process. By using this phase the energy consumption of the node is reduced. In the set-up phase the base station disseminate the message to all the node and help the random node to form a cluster within the cellular network. At last the steady-state phase is executed merely once ahead the set-up phase in the process of cellular network. Simulation result shows the comparison between LEACH and G-LEACH and energy consumed by the each node in the cellular network.